Analysis of elite football players serving in leagues from the perspective of squad-league networks: A case study of FIFA world cups from 1950 to 2022 - Yang, C.; Ma, R.; Exel, J.; Pyta, W.; Lames, M. (Scientific Journal of Sport and Performance, 2025)
This study introduces the "Squad-League Networks" (SLN) methodology to explore the globalization of elite football player mobility between national teams and domestic leagues from 1950 to 2022. By constructing longitudinal networks based on FIFA World Cup data, the research aims to uncover global trends and structural patterns in player movements, with a particular focus on recent decades. The dataset includes elite players who participated in each World Cup tournament, capturing their affiliations with both squads and leagues. The analysis reveals a growing trend of globalization, with player flows increasingly extending beyond traditional North-South routes to more diverse and multidirectional pathways. Notably, a Matthew effect emerges: leagues with higher initial attractiveness continue to draw more elite players, leading to concentrated mobility and reinforcing existing hierarchies. These findings highlight the dynamic and uneven nature of global football labour markets. The study offers new insights for sports managers and policymakers, suggesting that understanding these mobility patterns can help strengthen the competitiveness of domestic leagues and guide policy responses to the challenges and opportunities posed by globalization in football. By integrating network analysis with historical data, the SLN approach provides a novel lens for examining long-term transformations in elite player distribution worldwide.